The Effectiveness of the Celebrity Advertisement Process and its Impact on Buying Intention - S., Sathyanarayana; Gargesa, Sudhindra; N., Bhavya (Indian Journal of Marketing, 2019)
It has been observed that advertisements with celebrities create a great influence among the younger generation. Marketers spend considerable amounts on celebrities based upon the belief that celebrity endorsed advertisements are reliable, and that they have the knowledge about the brand, product recall, instant awareness, and retention of the products (Cooper, 1984) is quite more in those brands endorsed by the celebrities. Therefore, the current study attempted to know the determinants of factors such as Attractiveness of the celebrity (X1), Celebrity credibility (X2), and Celebrity expertise (X3) that determined the buying intention of the respondents. A sample size of 220 respondents was considered for the purpose of the study. On performing detailed analysis, patterns from the data were further put for validation through testing of hypotheses, whichever we deemed important and based upon the conditions set for such test. The study revealed that the brand ambassadors played an important role in boosting the sales. The study further found that products advertised with brand ambassadors had a large impact upon the buying behavior. Majority of the respondents perceived celebrities’ physical attractiveness as the major factor in celebrity advertisements. The respondents preferred a celebrity to be attractive in his/her physical appearance, to wear stylish clothes according to latest fashion trends, and to have an elegant presence.